Resolving a search for words as an interactional resource for achieving professional activity goals - Taquechel-Chaigneau, Roxana (Linguistica Atlantica, 2014)
This is an analysis of several interactions arising during two multilingual professional meetings convened in two international companies, one in Paris and the other in Beijing. Through the compilation of word searching attempts during interactions in ELF (English as lingua franca) we shall show how the participants orient themselves individually or collectively to resolve their verbal difficulty. It has been observed that, in ordinary conversations, when a linguistic and interactional problem emerges (Schegloff et al. 1977; Gülich 1986), the participants use certain methods to solve difficulties such as lexical production (Goodwin & Goodwin 1986; Brouwer 2003), or the adequacy of the linguistic forms to the current interactive activity. These methods are primarily based on the preference for self-repair (Schegloff 1977) and for progressivity (Stivers & Robison 2006). The preference for self-repair can take different cooperation forms to resolve an interactional problem. The other-repair phenomenon becomes the collective form to ensure the progress of the activity, to which all participants contribute in an ordered way. It can have consequences for participation frameworks, which are modified to solve a specific problem, and resume the main activity.